Census of the population 1910 - Occupational groups - Brantgärde, Lennart (University of Gothenburg, 1991)
This data collection contains information about population within the principal occupational groups agriculture, industry and mining, commerce, transport, storage and communication, public service, domestic work and unspecified occupation, and also within subgroups of these principal groups.

This data collection contains information about population within the principal occupational groups agriculture, industry and mining, commerce, transport, storage and communication, public service, domestic work and unspecified occupation, and also within subgroups of these principal groups.
Folkräkningen 1910 - Yrkesgrupper
Keywords: occupations; yrken; population; befolkning; census data; folkräkningsdata; rural population; landsbygdsbefolkning; urban population; stadsbefolkning; Censuses; Folkräkningar; Employment; Sysselsättning; HISTORY; HISTORIA; History; Historia